Deletion of ttrA and pduA genes in Salmonella enterica serovars induce a comparable immune response to wild-type infection in different chicken lineages - de Lima, Túlio Spina [UNESP]; Souza Saraiva, Mauro de Mesquita [UNESP]; de Almeida, Adriana Maria [UNESP]; Ferreira, Taisa Santiago [UNESP]; Rodrigues Alves, Lucas Bocchini [UNESP]; Ferreira, Viviane Amorim [UNESP]; de Freitas Neto, Oliveiro Caetano; Barrow, Paul Andrew; Berchieri Junior, Angelo [UNESP] (Taylor & Francis, 2025)
It was previously reported that utilization of tetrathionate and 1,2-propanediol by Salmonella spp. through the metabolic pathways encoded by ttr and pdu operons are related to overgrowth and out-competing microbiota in an anaerobic environment. However, recent knowledge demonstrated which strains in the absence of ttr and pdu genes provoke both higher intestinal colonization and spreading of bacteria in faeces compared with their respective wild-type strain, and also generate more prominent inflammation. This study evaluated the immune response of different lineages of chicks infected by Salmonella Typhimurium (STM) and Salmonella Enteritidis (SE) with ttrA and pduA gene deletions. Our work was separated into two experiments, one for each strain, utilizing 108 chicks to collect spleen and caecal tonsils for measuring immune response through RT-qPCR. From the immune response analysis, Salmonella Enteritidis mutant and wild-type strains elicited upregulated pro-inflammatory cytokines on the first-day post-infection; the opposite occurred with Salmonella Typhimurium strains (mutant and wild-type). However, the deletions did not impair the immune response produced by mutant strains compared with the respective wild-type in the caecal tonsil and spleen, suggesting that these metabolic pathways are not essential for colonization success. In conclusion, SE and STM, in the absence of ttrA and pduA genes, provoke an immune response with the same intensity as respective wild-type strains. RESEARCH HIGHLIGHTS: ttrA and pduA double mutants in Salmonella provoke a similar immune response. SE elicited more intense immune responses than STM. The immune response in the broiler was more intense than in other lineages.
Keywords: 1,2-propanediol; cytokines; immune response; Salmonella Enteritidis; Salmonella Typhimurium; tetrathionate